Biological Dosimetry Using Micronucleus Assay in Simulated Partial-Body Exposure to Ionizing Radiation - S. Purnami; S. Nurhayati; M. Syaifudin; D. Ramadhani (Atom Indonesia, 2017)
In radiation accidents, it is common that only several parts of the body are exposed to radiation. As a consequence there is a mixture of exposed and unexposed lymphocytes in peripheral blood cells of the samples. This phenomenon will cause the dose value estimated using the exposed lymphocytes to be lower than the actual dose. In this study, an assessment of partial body exposures using micronucleus assay by estimating the partial body dose and fraction of irradiated blood was conducted. An optimal D0 value also has been determined in this study to estimate the fraction of irradiated cells. Peripheral blood lymphocytes (PBLs) from three healthy donors were irradiated in vitro with 2 Gy of X-rays. Partial radiation exposure was simulated by mixing the irradiated and non-irradiated blood in different proportions. The proportions of mixtures of blood samples irradiated in vitro were 5, 10, 15, 20, and 30 %. Blood samples were then cultured and harvested based on micronuclei assay protocol. At least 2000 binucleated cells with well-preserved cytoplasm were scored for the MN frequency. Dose Estimate 5.1 software was used to calculate the dispersion index (σ2/y) and normalized unit of this index (U) in each proportion of bloods. The fractions of irradiated cells were calculated with CABAS (Chromosomal Aberration Calculation Software) for several different D0 values (2.7; 3.8; 5.4). The results showed that D0 value at 5.4 gave the closest results to the actual proportion of irradiated bloods, while for the dose estimation the estimated doses value from all proportions in all donors were higher than the actual dose. The factor that may cause this phenomenon was that the dose response calibration curve used to predict the radiation dose was not constructed in the laboratory used. Overall it can be concluded that a biodosimetry using MN assay can be used to estimate the radiation dose in partial body exposure. In order to establish a biodosimetry using MN analysis the dose-response calibration curve MN analysis should be constructed first in the laboratory used.